University Students’ Rejection to Learning Statistics: Research from a Latin American Standpoint - Valentina Ramos; Jorge Cruz-Cárdenas; Mónica Bolaños-Pasquel; Carlos Ramos-Galarza (Emerging Science Journal, 2023)
Introduction: Negative beliefs, fear, avoidance behaviors, and superficial attitudes surrounding the learning of statistics create significant problems for university students in Latin America. Objective: To analyze the impact of fearful behavior, superficial work, and avoidance displayed by university students when it comes to statistics. Method: In this article, we give details about a quantitative research project carried out by two independent studies. The first (N = 310) focused on the development of a scale to assess negative beliefs, fears, and avoidance behaviors towards statistics, in which goodness of fit was determined in a 3-factor model. In the second study (N = 250), it was hypothesized that undergraduates perform superficially due to negative beliefs and avoidance behaviors when learning statistics. Findings: The proposed model explained 42% of the variance. In addition, in the analysis of the proposed mediation model, an adequate adjustment was found. In the discussion of this research project, the need to intervene in the negative beliefs, fears, and avoidance behaviors displayed by university students towards statistics is highlighted. Novelty:This research project explains why college students dislike or avoid learning statistics in depth. The findings will allow for a modification in the way statistics is taught so that Latin American professionals achieve better performance in this field. Doi: 10.28991/ESJ-2023-SIED2-07 Full Text: PDF